Adult Care in Cystic Fibrosis - Elborn, J. Stuart (Seminars in Respiratory and Critical Care Medicine, 2019)
Cystic fibrosis (CF) is now more common in adults than children in countries with well-developed health care systems. The number of adults continues to increase and will further increase if the new cystic fibrosis transmembrane conductance regulator (CFTR) modulators are disease modifying. Most of the complex morbidity and almost all the mortality of CF occur in adults and will increasingly follow this pattern even with new effective modulator therapies. Maintaining good quality of life including social functioning and maximizing survival for adults are the key priorities. This requires a highly knowledgeable and adaptable multidisciplinary team, which, though focused on maintaining lung health, requires an increasing range of other disciplines and specialties to maximize well-being. Changes in health care systems will require current models of care to adapt to provide care for the large number of adult patients. With increasing survival and age, many are likely to have both CF morbidities and additional diseases of aging. New models are needed for health care delivery for this expanding population with complex medical conditions.
Keywords: cystic fibrosis; adults; multidisciplinary team; CFTR dysfunction; comorbidities